Scientific output of undergraduate research supervisors: the role of sex-related, academic career, and subject areas in a Brazilian public institution - Costa, Woska Pires da; Walker, Angélica Ferreira Melo; Miñana-Signes, Vicente; Monfort-Pañego, Manuel; Noll, Priscilla Rayanne E. Silva; Noll, Matias (Frontiers in Education, 2025)
IntroductionThis research explores how various characteristics influence supervisors’ research output and engagement. It focuses on undergraduate research (UR) programs at a Brazilian federal educational institution. The study examines academic curricula, including the number of publications and the impact of their productions, and looks for possible academic inequalities. Accordingly, it analyzes the influence of sex-related, academic path, and subject areas on the productivity of UR supervisors in this institution.MethodsA case study approach was employed, utilizing quantitative methods for data collection. Data was collected on diverse variables, such as education, academic trajectory, publications, patents, and supervisory roles, by examining the administrative records and the data registered in the Lattes Curriculum platform. Descriptive and inferential statistics, including non-parametric tests and correlation analyses, were employed for data analysis, offering insights into the characteristics and contributions of UR supervisors at the undergraduate level.ResultsThe study included 307 supervisors (59.0% of men), primarily in the Agrarian Sciences (51.5%), aged 37–46 years, and holding doctorate degrees (78.8%). Notably, supervisors in the Agrarian Sciences area had the highest mean experience in UR supervision (51.5%). Statistical analyses revealed significant differences among supervisors based on their research area and between supervisory activities, more prominently in research outputs and impact measures (p < 0.001) for master’s studies supervisions. On average, supervisors had 2.19 articles per year, with higher productivity in the Health Sciences followed by the Biological Sciences field. A positive difference (18.0%) in supervisor participation was found between males and females, with men having a higher rate (14.7%), consistent with previous studies.ConclusionThe investigation emphasizes addressing sex disparities and promoting scientific research to enhance academic output indicators through public policies. This analysis provides valuable insights for fostering public policies directed toward educational institutions.Ethics and disclosureThe Research Ethics Committee approved the study, ensuring the confidentiality of participant data and compliance with ethical standards.